2020
DOI: 10.1086/706786
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Incubation Temperature Independently Affect Embryonic Development and Offspring Size in a Turtle with Temperature-Dependent Sex Determination

Abstract: Developmental environments can have lasting effects on an individual's phenotype. In many reptiles, for example, egg incubation temperature permanently determines offspring sex (temperature-dependent sex determination, TSD) and also influences a suite of morphological, physiological, and behavioral traits. Thus, the contributions of sex and incubation temperature to phenotypic variation are difficult to identify because these factors are confounded under TSD. We used chemical manipulations to experimentally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Although we found no evidence for sex effects on hatching success and post-hatching survival in this study, we see a cumulative reduction in fitness for females across all three stages (Table 2). Sexspecific differences in survival have been documented in other turtle species (e.g., Steyermark and Spotila, 2001b;Freedberg et al, 2001Freedberg et al, , 2004, as well as a range of other traits in painted turtles (Warner et al, 2020). In species with TSD, sex and temperature effects on lifehistory traits are often confounded, and the absence of statistically Frontiers in Physiology frontiersin.org significant sex effects on survival at each stage in this study may be due to the thermal variance incorporated through temperature switches, which could have produced intermediate phenotypes and thus blurred group distinctions.…”
Section: Discussionmentioning
confidence: 97%
“…Although we found no evidence for sex effects on hatching success and post-hatching survival in this study, we see a cumulative reduction in fitness for females across all three stages (Table 2). Sexspecific differences in survival have been documented in other turtle species (e.g., Steyermark and Spotila, 2001b;Freedberg et al, 2001Freedberg et al, , 2004, as well as a range of other traits in painted turtles (Warner et al, 2020). In species with TSD, sex and temperature effects on lifehistory traits are often confounded, and the absence of statistically Frontiers in Physiology frontiersin.org significant sex effects on survival at each stage in this study may be due to the thermal variance incorporated through temperature switches, which could have produced intermediate phenotypes and thus blurred group distinctions.…”
Section: Discussionmentioning
confidence: 97%
“…However, in contrast to the results presented here, the same study showed that turtle hatchlings from the lower, MPT exhibited increased survival relative to their male counterparts incubated under intermediate temperatures promoting the development of both sexes (Janzen, 1995). Clearly, additional studies examining the extent to which incubation temperature influences juvenile survival under field conditions (Janzen, 1995; Warner et al, 2020) and the directionality of this relationship with respect to sex biases in age at maturity are needed to generalize across reptiles exhibiting TSD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the non-linear relationship explains studies where exogenous application of E 2 has unexpectedly produced male hatchlings (e.g. 43,44 ). In such cases, E 2 application, combined with existing maternal contributions, may have resulted in shifting the E 2 :T ratio within the eggs closer to one, forcing male development.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the effects of these hormones on sex determination vary by experiment and species, likely as the results of adaptation to local nesting conditions (e.g. 43,44 ). However, here we show that in sea turtles, a clutch specific threshold exist for feminisation that is the product of an interaction between temperature and maternal hormone transfer.…”
Section: Discussionmentioning
confidence: 99%